Physical fitness and motor competence tests as predictors of talent in soccer? The correlation of juvenile test results and later success viewed stepwise over 12 years - a longitudinal study - Siener, M.; Hohmann, A. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: There are already several studies on talent identification in youth soccer. However, only a minority of these studies have a longitudinal design or observe the complete performance trajectory of young athletes all the way to adulthood. The few studies that investigated associations between youth performance and later success in senior competitive sports showed that the validity of talent predictions steadily decreased with increasing time periods. However, the data available to date is very limited. Therefore, the aim of this study was to analyze the correlations of early test performance (physical fitness and motor competence tests) of young soccer players with their later successes stepwise over 12 years until adulthood.